A Comparative Characterization of Different Host-sourced Lactobacillus ruminis Strains and Their Adhesive, Inhibitory, and Immunomodulating Functions - Yu, Xia; Åvall-Jääskeläinen, Silja; Koort, Joanna; Lindholm, Agneta; Rintahaka, Johanna; von Ossowski, Ingemar; Palva, Airi; Hynönen, Ulla (Frontiers in Microbiology, 2017)
Lactobacillus ruminis, an autochthonous member of the gastrointestinal microbiota of humans and many animals, is a less characterized but interesting species for many reasons, including its intestinal prevalence and possible positive roles in host–microbe crosstalk. In this study, we isolated a novel L. ruminis strain (GRL1172) from porcine feces and analyzed its functional characteristics and niche adaptation factors in parallel with those of three other L. ruminis strains (a human isolate, ATCC 25644, and two bovine isolates, ATCC 27780 and ATCC 27781). All the strains adhered to fibronectin, type I collagen, and human colorectal adenocarcinoma cells (HT-29), but poorly to type IV collagen, porcine intestinal epithelial cells (IPEC-1), and human colon adenocarcinoma cells (Caco-2). In competition assays, all the strains were able to inhibit the adhesion of Yersinia entercolitica and enterotoxigenic Escherichia coli (ETEC, F4+) to fibronectin, type І collagen, IPEC-1, and Caco-2 cells, and the inhibition rates tended to be higher than in exclusion assays. The culture supernatants of the tested strains inhibited the growth of six selected pathogens to varying extents. The inhibition was solely based on the low pH resulting from acid production during growth. All four L. ruminis strains supported the barrier function maintenance of Caco-2 cells, as shown by the modest increase in transepithelial electrical resistance and the prevention of dextran diffusion during co-incubation. However, the strains could not prevent the barrier damage caused by ETEC in the Caco-2 cell model. All the tested strains and their culture supernatants were able to provoke Toll-like receptor (TLR) 2-mediated NF-ĸB activation and IL-8 production in vitro to varying degrees. The induction of TLR5 signaling revealed that flagella were expressed by all the tested strains, but to different extents. Flagella and pili were observed by electron microscopy on the newly isolated strain GRL1172.